Analise de instrumentos econômicos relativos aos serviços de resíduos sólidos urbanos - Brusadin, Mauricio Benedini (2003)
The developed research focuse an analysis of the concepts that permeate the creation of the Rate of Urban Solid Residues. It detached the basic notions that permeate this theme, from the sustentability concept, as well as the technical variables and politics that involve the idea of the Environmental Rates. Due to the width of the theme and to the multiple variables that surround it, we based our research on two fronts: the theoretical, seeking to consider that several ideas and notions that permeate the theme; and other practice, that was the study of the experiences adopted in several municipal districts to carry out the Rate of Urban Solid Residues. We can highlight by those fronts that, in the theoretical part, we revised a vast bibliography regarding the economical instruments used for elaboration of public politics heading for the sustainable development; already in the practical part, we searched to establish some differences of adoption of these instruments and their juridical consequences of being implemented. Being like this, we can establish that the Rate of Urban Solid Residues is characterized as a necessary measure to set out the problems faced by the Municipal Public Powers with relationship to the produced garbage . However, for the complexity of the calculation base for collection, for the juridical aspects that orientate it and, why not to say, for the political difficulties to their implementation, it is necessary to go deeper into these studies, so that, through a deeper knowledge of the Theme, our Political Representatives as well as the technicians that elaborate the public politics can step in a less loamy soil, avoiding, thus, so many unnecessary wastes.